IMPACT OF CROP CONDITION REPORTS ON NATIONAL AND LOCAL WHEAT MARKETS. (23rd December 2016) - BAIN, RYAN; FORTENBERY, T. RANDALL
Abstract: The U.S. Department of Agriculture (USDA) releases crop condition reports detailing crop progress and growing conditions for various crops including corn, soybeans, and winter wheat. Previous research has investigated market impacts from various USDA reports, but crop condition reports have received little attention. This article investigates the impact of crop condition reports on winter wheat prices at the national level and for a local market. We employ both parametric and nonparametric tests. Results suggest that crop condition reports for winter wheat do not generally affect market prices. This contrasts with results found in corn and soybean markets.